Safety climate analysis at two thermal power plants - Marhoon, Basil; Y. Abdalla, Ahmed (International Journal of Engineering and Technology, 2021)
The present work evaluates the safety climate as it reflects safety culture and is considered as a fast tool for assessing safety culture with minimum resources required. The evaluation is done for a private thermal combined cycle power company, Plant A. Another private company is also producing electric energy and water desalination, Plant B. Both plants are in Bahrain and under the management of one company. The evaluation is done through questionnaires, including all the staff of 210 employees. The questionnaire used in the present work is based on Nordic Safety Climate Questionnaire (NOSACQ-50) and modified by the help of the health and safety department of Plant A to be suitable to the power plant. Also, interviews are conducted to validate and support the questionnaire. Analysis has been done by different statistical methods using Microsoft Excel. The overall safety climate level of the two plants was found to be above average. The overall mean score of all results is 3.67 on a scale of 1 to 5. The mean score for most of the dimensions was higher than 3, which is considered a positive result. The level of safety for the daytime workers was found to be greater than the safety level of the shift workers. Also, the study reveals some factors that affect the safety climate level, such as, the nature of the work, the experience and the number of safety workshops attended.Â Â